The Effect of Fraud Hexagon on Financial Statement Fraud with Corporate Governance as a Moderating - Hardila, Ika; Widiyati, Dian; Holiawati (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2026)
The rapid dynamics of the business environment and the increasing cases of financial statement fraud highlight the importance of strengthening internal control mechanisms within companies. This study aims to analyze the effect of the fraud hexagon on financial statement fraud, with corporate governance serving as a moderating variable, in companies listed on the Indonesian Institute for Corporate Directorship (IICD) during the period 2022–2024. The research employed an associative quantitative method using secondary data obtained from the companies’ annual reports and financial statements. The sample was selected using purposive sampling, resulting in 51 observations. Data analysis techniques included panel data regression and Moderated Regression Analysis (MRA) with the assistance of EViews 12 software. The results indicate that the rationalization and capability variables significantly affect financial statement fraud, while financial stability, external pressure, opportunity, ego, and collusion have no significant effect. Moderation testing results show that corporate governance is able to moderate the relationship between rationalization and financial statement fraud but cannot moderate the relationships of other fraud hexagon variables. Overall, the fraud hexagon variables significantly influence financial statement fraud. These findings suggest that financial statement fraud is driven by a combination of financial, structural, and behavioral factors, and indicate that the role of corporate governance still has limitations in controlling certain elements of the fraud hexagon.